Adequacy Levels of Micronutrient as Risk Factors of Stunting in Toddlers in Pardasuka Village - Dewi, Afiska Prima; Muharramah, Alifiyanti; Wati, Desti Ambar; Wati, Hilda Widya (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Nutrition problems that are indicated by body size which is shorter than the toddlers' age are called stunting. Where the results of the pre-survey on 10 stunting toddlers in Pardasuka Village obtained an average level of vitamin A, zinc, and iron adequacy that is less than the RDA. The purpose of this study was to determine differences in adequacy levels of micronutrients (vitamin A, zinc, and iron) in toddlers aged 24-59 months with stunting and non-stunted conditions in Pardasuka village. The design used in this study was a case-control approach. The sample in this study amounted to 56 toddlers. Bivariate analysis in this study used the Chi-Square Test. Result : The results showed that there were differences between the case group and control group in vitamin A adequacy level with OR = 3.029 and p-value less than 0.05, zinc adequacy level with OR = 2,400 and p-value less than 0.05, and adequacy level iron value OR = 3.100 and p-value less than 0.05. Conclusion : there are differences in consumption patterns, levels of adequacy of macronutrients and micronutrients in stunted and non-stunted toddlers in Pekon Pardasuka